Influence of heat treatment on the phase transformation, thermodynamical parameters, crystal microstructure, and of Cu-Al-X (X: Cr, Ti) shape memory alloys - Ateş, Gonca; Öner, Ecem Özen; Kanca, Muhammed Sait (Niyazi BULUT, 2022)
Shape memory alloys are known for their ability to return to their original shape under the influence of external factors (temperature, magnetic field and mechanical stress). Although NiTi-based alloys come to mind first when the shape memory effect is mentioned, CuAl-based alloys are very popular alternatives. The low cost of copper-based alloys is the biggest reason to study. In this study, the heat treatment effects of Cu-Al-X (X: Cr, Ti) (% weight) on some thermodynamic parameters, crystal structure and microstructure of shape memory alloy were investigated at three different temperatures (973 K, 1073 K and 1173 K). The changes in the thermal transformation of the samples were determined by DSC (Differential Scanning Calorimetry) and the changes in the crystal structure were determined by X-ray diffraction (XRD), Scanning Electron Microscope (SEM) and optical microscope device. According to DSC measurement, the temperature hysteresis of the samples decreased after the heat treatment. Besides, as the entropy change decreased, the thermal stability of the samples increased. It can be seen that the particle size of the CuAlCr alloy decreased with increasing temperature. The particle size of the CuAlTi alloy increased with increasing temperature. SEM and optical images showed that chromium (Cr) was more dissolved in the alloy compared to titanium (Ti) into CuAl alloy.
Keywords: Material Production Technologies; Malzeme Üretim Teknolojileri